New species of Otiothopinae (Araneae: Palpimanidae) from Colombia - Cala-Riquelme, Franklyn; Quijano-Cuervo, Luis; Sabogal-González, Alexander; Agnarsson, Ingi (Zootaxa, 2018)
Six new Colombian species of Otiothops (O. besotes sp. n., O. doctorstrange sp. n., O. chicaque sp. n., O. vaupes sp. n.) and Fernandezina (F. andersoni sp. n., F. eduardoi sp. n.) are described. Diagnostic illustrations and distribution maps are provided for all of the new species, along with new records for O. macleayi Banks, 1929 and O. amazonicus Simon, 1887 from Colombia.